Antidepressant Prophylaxis Reduces Depression Risk but Does Not Improve Sustained Virological Response in Hepatitis C Patients Receiving Interferon Without Depression at Baseline: A Systematic Review and Meta-Analysis - Awad Al-Omari; Juthaporn Cowan; Lucy Turner; Curtis Cooper (Canadian Journal of Gastroenterology)
BACKGROUND: Depression complicates interferon-based hepatitis C virus (HCV) antiviral therapy in 10% to 40% of cases, and diminishes patient well-being and ability to complete a full course of therapy. As a consequence, the likelihood of achieving a sustained virological response (SVR [ie, permanent viral eradication]) is reduced.